Synthesis of isoquinoline and pyrocatechol derivatives as potential drug molecules active against prostate cancer - Zengin, Elif. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Prostate cancer is one of the most common cancer types among male worldwide. It has been found that about 80 percent of prostate cancer patients have high level of androgen levels. Prior researches have stated that reducing the androgen level in the body can be a good solution to prevent the growth of cancer cells. Androgens are synthesized in both testes and adrenal glands. Hence, inhibition of androgen biosynthesis in not only testes, but also adrenal glands is essential to suppress the androgen biosynthesis. The last step of androgen biosynthesis in both testes and adrenal glands is catalyzed by a single enzyme, 17α-hydroxylase-17,20-lyase (CYP17). On account of this information, selective inhibition of CYP17 enzyme results in reduction or complete annihilation of androgen production. Thus, CYP17 is the foremost target enzyme for the treatment of prostate malignancy. Accordingly, computational screening method was used to find out lead compounds active against CYP17 enzyme by Prof. Metin Türkay and Assoc. Prof. Halil Kavaklı from Koç University. As a result of the drawbacks of steroidal compounds, a non-steroidal lead compound with an IC50 value of 35 μM was found. In order to find compounds with better IC50 values, derivatives of the lead compound were examined by using Autodock program. Among the derivatives, the compounds with better docking and binding energies were synthesized. In this project, synthesis of isoquinoline and pyrocatechol derivatives was targeted. For this purpose, ten compounds were synthesized. Biological tests were performed by the research group of Assoc. Prof. İbrahim Halil Kavaklı from Koç University. As a result, a new compound with hundred percent inhibition at 5 μM concentration was discovered.
Keywords: Prostate -- Cancer.; Isoquinoline.; Catechol.